Development of gluten-free and egg-free pasta based on quinoa (Chenopdium quinoa Willd) with addition of lupine flour, vegetable proteins and the oxidizing enzyme POx - Linares-García L. (2019)
The aim of this research was to develop gluten-free (GF) and egg-free quinoa pasta with high nutritional value. Extruded and non-extruded quinoa (red and white) flour, potato starch, tara gum, and potato, pea and rice protein isolates were investigated in different recipes, some of them included egg white as an initial reference point. Results showed that extruded quinoa flour, potato starch and tara gum had deteriorating effects on GF and egg-free pasta firmness and cooking quality. Lupine flour addition itself was not able to replace egg white when added in the same amounts, but after increasing the concentration to 12%, the firmness and cooking quality decreasing effects could be improved again, especially when tara gum was absent in the formulations. In the final recipe, the content of lupine flour was increased to 30% because its protein is complementary to the quinoa protein. From the three studied protein isolates, pea protein was superior to potato or rice protein, addition of the oxidizing enzyme POx could even further improve texture firmness. After these trials, the final recipe containing lupine flour, pea protein and POx showed satisfying GF noodle quality and possessed a valuable nutritional composition with high protein and dietary fibre content. © 2019, The Author(s).